2007
DOI: 10.1167/7.12.1
|View full text |Cite
|
Sign up to set email alerts
|

The perception of suprathreshold contrast and fast adaptive filtering

Abstract: We examine how the perceived contrast of dynamic noise images depends upon temporal frequency (TF) and mean luminance. A novel stepwise suprathreshold matching paradigm shows that both threshold and suprathreshold contrast sensitivity functions may be described by an inverted-U shape as a function of TF. The shape and the peak TF of the tuning function vary with the conditions under which it is measured. Spatiotemporal vision is weakly band-pass at low luminance levels (0.8 cd/m(2)) but becomes more strongly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 71 publications
5
51
0
Order By: Relevance
“…Early studies found that apparent contrast did not depend on spatial and temporal frequencies of luminance modulation: a phenomenon called “contrast constancy” (Georgeson & Sullivan, 1975; Georgeson, 1987; Webster, Georgeson, & Webster, 2002). Recent studies contested this conclusion, however, and found that apparent contrast did vary across spatiotemporal frequencies, reflecting the perception near threshold (Bex & Langley, 2007; Smith, 2015). Our finding that perception of suprathreshold stimuli varies across spatiotemporal stimuli agrees with the observations of failure of contrast constancy.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that apparent contrast did not depend on spatial and temporal frequencies of luminance modulation: a phenomenon called “contrast constancy” (Georgeson & Sullivan, 1975; Georgeson, 1987; Webster, Georgeson, & Webster, 2002). Recent studies contested this conclusion, however, and found that apparent contrast did vary across spatiotemporal frequencies, reflecting the perception near threshold (Bex & Langley, 2007; Smith, 2015). Our finding that perception of suprathreshold stimuli varies across spatiotemporal stimuli agrees with the observations of failure of contrast constancy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar gap effect has been found by many other studies (Schiller et al, 1987; Munoz et al, 1998; Bucci et al, 2005; Yang and Kapoula, 2006; Yang et al, 2006). This result can be explained by the release of the fixation in the gap task; competition between the two points (central versus peripheral) leads to a latency increase in the overlap task (Dorris et al, 1997; Rolfs and Vitu, 2007). Advanced motor preparation in the gap task is another mechanism (Rolfs and Vitu, 2007; Vernet et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Latencies are 40–110 ms shorter in the gap task. This effect called “gap effect” (Saslow, 1967) is believed to be related to advance movement preparation due to release of the oculomotor fixation in the gap task (Rolfs and Vitu, 2007). It is believed that in the gap task, saccade initiation is triggered by the posterior parietal cortex (PPC; Pierrot-Deseilligny et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Whenever a stimulus property was found to influence the probability of perceptual dominance during BR it was added to a grab bag of characteristics collectively termed signal strength. However, close inspection of this grab bag reveals that many features within it could be used to differentiate images of selective obstructions from images of more distant objects (see Fahle, 1982a,b; Arnold et al, 2007; Changizi and Shimojo, 2008). …”
Section: Signal Strengthmentioning
confidence: 99%
“…Similarly, blurring an image reduces image contrast (Fahle, 1982a,b), and both luminance and chromatic contrasts contribute to signal strength (Levelt, 1968; Mueller and Blake, 1989; Kovacs et al, 1996; Pearson and Clifford, 2004). Clearly signal strength, or at least a number of characteristics grouped under this term, would be useful for a process that strives to suppress awareness of selective obstructions in order to enhance the visibility of more distant objects (Fahle, 1982a,b; Arnold et al, 2007; Changizi and Shimojo, 2008). So another reason BR is uncommon is that the images of selective obstructions have a very low signal strength.…”
Section: Signal Strengthmentioning
confidence: 99%